2021
DOI: 10.1038/s41419-021-03741-5
|View full text |Cite
|
Sign up to set email alerts
|

ADIPOR1 deficiency-induced suppression of retinal ELOVL2 and docosahexaenoic acid levels during photoreceptor degeneration and visual loss

Abstract: Lipid metabolism-related gene mutations can cause retinitis pigmentosa, a currently untreatable blinding disease resulting from progressive neurodegeneration of the retina. Here, we demonstrated the influence of adiponectin receptor 1 (ADIPOR1) deficiency in retinal neurodegeneration using Adipor1 knockout (KO) mice. Adipor1 mRNA was observed to be expressed in photoreceptors, predominately within the photoreceptor inner segment (PIS), and increased after birth during the development of the photoreceptor outer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 52 publications
1
35
0
Order By: Relevance
“…Mutations in ADIPOR1 have been associated with retinitis pigmentosa [18,19] and agerelated macular degeneration [22]. While studies suggest that both ADIPOR1 and MFRP participate in docosahexaenoic acid (DHA, 22:6) enrichment [23] and lipid homeostasis in RPE and PR cells [24], there is still an incomplete understanding about the function of the individual proteins and their potential functional association and interaction that lead to similar disease phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in ADIPOR1 have been associated with retinitis pigmentosa [18,19] and agerelated macular degeneration [22]. While studies suggest that both ADIPOR1 and MFRP participate in docosahexaenoic acid (DHA, 22:6) enrichment [23] and lipid homeostasis in RPE and PR cells [24], there is still an incomplete understanding about the function of the individual proteins and their potential functional association and interaction that lead to similar disease phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, ADIPOR1 was expressed in the retina as reported. 20 , 21 In vivo studies showed that the expression of CTRP9 transcripts is relatively restricted to adipose tissues. The adiponectin and CTRP9 transcripts are rarely expressed in the eye.…”
Section: Discussionmentioning
confidence: 99%
“…Although AdipoR1-KO embryos/MEFs showed a relatively mild membrane defect phenotype, the consequences of AdipoR1 mutations can still be dramatic in the adult or in specific tissues. For instance, single amino acid mutation of AdipoR1 occurs in different forms of retinitis pigmentosa 57, 58 and AdipoR1-KO mice have a substantial degeneration of photoreceptors and visual impairment as early as 3 weeks of age that is due to the lack of PUFA in membrane phospholipids 54, 55 . This provides an independent confirmation that the AdipoR pathway is essential for membrane homeostasis, and shows that AdipoR1 has a specialized role in the maintenance of PUFA levels in the retina.…”
Section: Discussionmentioning
confidence: 99%